Strain rate effect on mode I debonding characterization of adhesively bonded aluminum joints - Khan, Safdar Ali; Rahimian Koloor, Seyed Saeid; King Jye, Wong; Yidris, Noorfaizal; Mohd Yusof, Ab Aziz; Mohd Szali Januddi, Mohd Al Fatihhi; Tamin, Mohd Nasir; Johar, Mahzan (Multidisciplinary Digital Publishing Institute, 2022)
In adhesive bonding, two different substrate materials are joined together, usually by forming chemical bonds. The adhesive can stick things together. The loading rate and deformation mode can easily change the mechanical properties of the adhesive material. Hence, a vital aim of the current study is to evaluate the strain rate effect on the damage response of adhesive joints for Mode I loading scenarios. The adherend material was aluminum AL6061-T6, and Araldite 2015 was the adherent material. This experiment for delamination had a prescribed adherend size of 200 mm × 25 mm × 3 mm and an adhesive thickness of 0.5 mm. In situations where the strain rate affects the failure mechanism, a displacement rate of 5, 50, or 500 mm/min is sufficient to attain the failure mechanism. A double cantilever beam (DCB) specimen was employed to construct the FE model geometry for simulation. A hybrid experimental–FE technique was utilized to extract the properties of the adhesive interface. FE simulation has proven to have an excellent correlation with the experimental findings.